Finite element analysis of rc beams with bamboo fiber reinforced composite plate using ABAQUS - Yip, Wai Kit (2017)
This research aims to investigate the behavior of reinforced concrete beams with and without openings, un-strengthened beams and beams strengthened using Bamboo Fiber Reinforced Composite Plate (BFRCP) externally at the flexural and shear zones. The objectives of this research was to determine the behavior of solid RC beams and RC beams with openings in terms of load-deflection and crack pattern in finite element analysis as well as the effect of strengthening after using bamboo fiber plate reinforced with polyester and vinyl ester in bending and shear zone. Lastly, the finite element analysis results were validated with the experimental results. A total of nine beams with a dimension of 120 x 300 mm and a length of 1500 mm were modelled as simple-supported beams in a three dimensional analysis using ABAQUS 6.14. In this research, two circular openings having diameter of 120 mm were located at the shear zone of the beams. The reinforcement bars were modelled as 10 mm diameter bars for both top and bottom reinforcement as well as 6 mm diameter stirrups with spacing of 100 mm center to center. From the finite element analysis results, the ultimate load for control beams was 247.5 kN, with a reduction of 14.4 % when shear links in the flexural zone were removed. On the other hand, a reduction of 64.8 % when openings were created in the beams. In terms of external strengthening with BFRCP, it was found that there was a regain of 4.6 % and 3.5 % when using BFRCP reinforced with polyester and vinyl ester, respectively. In addition, when an additional length of the composite plate was used, there was an increment of 8.7 % and 6.1 %, respectively. As for beams with openings, the load capacity had increased 52.6 % and 52.1 % after the external strengthening was simulated using polyester and vinyl ester resins, respectively. The validation with experimental results using finite element analysis showed a less than agreeable results, however, the crack patterns showed good agreement between the results of finite element analysis and experimental results.